What is the Baitul Maal wat Tamwil Inbound Marketing Model in Indonesia? - Hendri Hermawan Adinugraha; Shulthoni, Muhammad; Syakirunni'am, Luqman (Mabny: Journal of Sharia Management and Business, 2023)
This study intends to describe practical models of inbound marketing at Baitul Maal Wat Tamwil (BMT). This research is an observational descriptive study on BMT in Indonesia, using the triangulation method. The total subjects recruited in the study were 50 BMT. This study uses primary data obtained based on structured interviews and in-depth interviews with BMT managers. Data analysis uses descriptive and qualitative analysis and is displayed in descriptive form. The findings of this study conclude that BMTs in Indonesia have used inbound marketing to inform and communicate with customers. Social media that is often used is Facebook, Whatsapp, Instagram, TikTok, and Twitter. The platform is quite effectively used in informing BMT products and interacting directly with customers. The benefit most felt by BMT is that communication with customers and customers is more intensive and effective and efficient because they can communicate directly in full and real-time. The strategy for implementing inbound marketing has proven to have a positive impact on BMT and its customers, inbound marketing has been able to increase sales of fundraising and financing products at BMT.